2021
DOI: 10.1101/2021.08.26.457884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A vimentin-targeting oral compound with host-directed antiviral and anti-inflammatory actions addresses multiple features of COVID-19 and related diseases

Abstract: Damage in COVID-19 results from both the SARS-CoV-2 virus and its triggered overreactive host immune responses. Therapeutic agents that focus solely on reducing viral load or hyperinflammation fail to provide satisfying outcomes in all cases. Although viral and cellular factors have been extensively profiled to identify potential anti-COVID targets, new drugs with significant efficacy remain to be developed. Here, we report the potent preclinical efficacy of ALD-R491, a vimentin-targeting small molecule compou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The in vivo studies suggested that ALD-R491 significantly reduces the lung damage and fibrosis. The above results indicate that ALD-R491 can be used to treat COVID-19 and can also reduce the recurrence due to its effects on the prevention and treatment of lung damage 11 .…”
Section: Small-molecule Drugsmentioning
confidence: 73%
See 1 more Smart Citation
“…The in vivo studies suggested that ALD-R491 significantly reduces the lung damage and fibrosis. The above results indicate that ALD-R491 can be used to treat COVID-19 and can also reduce the recurrence due to its effects on the prevention and treatment of lung damage 11 .…”
Section: Small-molecule Drugsmentioning
confidence: 73%
“…ALD-R491 exerts antiviral and anti-inflammatory dual effects by targeting vimentin. Vimentin has a role in the entry, intracellular transport, and release of the virus, as well as an inflammatory response 11 . ALD-R491 can reduce endocytosis, endosomal transport and exosome release, thus preventing the virus from entering or leaving cells.…”
Section: Small-molecule Drugsmentioning
confidence: 99%
“…The importance of endosomal morphology and function for SARS-CoV-2 entry was demonstrated in a study reporting alteration of intermediate filaments (IF) to affect both entry and egress steps of SARS-CoV-2 (Li et al, 2021c) (Figure 1). Using the pharmacological inhibitor ALD-491 targeting the class III IF vimentin, the authors reported reduced SARS-CoV-2 entry and exosomal release in cell culture-based assays as well as mitigated disease severity and lung damage in aged mice.…”
Section: Endosomal Trafficking and Sars-cov-2 Entrymentioning
confidence: 99%
“…Infection alters the architecture of the ER and the network of DMVs was found to be surrounded by a ‘cage‐like’ vimentin network and pharmacological inhibition of intermediate filaments with Withaferin A reduced SARS‐CoV‐2 replication (Cortese et al., 2020). Of note, vimentin appears to have a dual role in the SARS‐CoV‐2 infection cycle, by contributing to viral entry (see section ‘ENDOSOMAL TRAFFICKING AND SARS‐COV‐2 ENTRY’, Figure 1) and egress of infectious virus particles (Li et al., 2021c). It has been shown that newly assembled ß‐coronaviruses exit the cells using lysosomal exocytosis with lysosomes being deacidified and lysosomal enzymes inactivated (Ghosh et al., 2020).…”
Section: Secretion and Exosomal Trafficking In Sars‐cov‐2 Infectionmentioning
confidence: 99%